The Effects of Natural Ventilation Techniques on Indoor Air Temperature for Urban Terrace Houses in oht Humid Climate - Gracie Vanessa Anak Jekop; Mohd Azuan Bin Zakaria (Recent Trends in Civil Engineering and Built Environment, 2021)
Natural ventilation is one of a techniques that could improve indoor thermal environment. In this day and age, urban terrace houses have been developed rapidly and it usually are hotter than the house in a rural area. The aim of the study is to compare the air temperature and relative humidity of indoor spaces by utilizing of day ventilation (case 1), night ventilation (case 2) and full day ventilation (case 3). The field measurement has been carried out in a single storey terraced housed for three days for each of the case study which consist of day ventilation (7a.m. to 7p.m.), night ventilation (7p.m. to 7a.m.) and full day ventilation (24 hours). The measurement was measured with Thermo Recorder TR-72U for air temperature and relative humidity. The sensor was placed at 1.5m above ground at the center of living room and bedroom. The result shows that case 2 which is night ventilation has the lowest air temperature measured in the urban terrace house during night-time. Case 2 shows a reduction of 6.3˚C for the maximum air temperature between indoor and outdoor air temperature compare to all cases. Night ventilation is the most recommended for the natural ventilation techniques application.